SELF-PERCEPTION OF BODY IMAGE IN EDUCATION COURSE UNDERGRADUATE PHYSICS OF A PUBLIC UNIVERSITY TERESINA-PI (Fiep Bulletin - online, 2017)
Body image is the mental representation of the body structure and physical appearance that an individual has ofhimself and toward others. The aim of this study was to evaluate the self-perception of body image in undergraduate physicseducation course at a public university of Teresina-PI. The research is descriptive, cross-sectional, qualitative and quantitative.The target audience of the research were 50 undergraduate freshmen and conclusive of the year 2016, 27 males and 23 females,aged 17-30 years who were willing to participate. Data were collected on the perception and dissatisfaction with body imagethrough the range of 15 silhouettes and validated questionnaire on body image Body Shape Questionnaire (BSQ). Most of thestudents (52%) presented themselves dissatisfied with thinness. By associating the BSQ variables and the range of silhouettes,the graduate students who had moderate distortion (75%), feel dissatisfied by excess; while those who did not distortion(61.76%), feel dissatisfied with thinness, although this association was not statistically significant (p = 0.107). We conclude thatthe prevalence of body image distortion in the surveyed graduate students was not significant in any of the observedassociations. Although this did not prevent the prevalence of dissatisfaction with body image in the direction of both genders wantto have your increased silhouette. Thus, there is importance of reflecting a guiding reflective praxis for future health professionalsand sports.
Keywords: Body image; body satisfaction; Graduate students